Does Hub‐and‐Spoke organization of healthcare system promote workers' satisfaction?. Issue 10 (31st July 2019) - Albarello, Flavia; Prati, Francesca; Sangiorgi, Luca; Tremosini, Morena; Menegatti, Michela; Depolo, Marco; Rubini, Monica
Abstract: The healthcare services network is a recent organizational structure of healthcare services that are interdependent and organized as a network on the basis of the Hub‐and‐Spoke model. This questionnaire‐based study analyzed socio‐psychological well‐being of health workers both in terms of team‐related experience and individual satisfaction and engagement with one's work in a Hub‐and‐Spoke healthcare service in comparison to non‐network healthcare service. Workers from two different public healthcare services involved in the treatment of the same skeletal rare diseases participated in the Study. We expected that working under a Hub‐and‐Spoke healthcare service—involving teamwork and cooperation among different healthcare services within the units, as well as among workers belonging to different units—would lead to greater psychological team‐related and individual benefits. In line with predictions, the findings showed that under a Hub‐and‐Spoke healthcare service, health workers felt highly interdependent by their team fellows and developed shared cognitions (i.e., team mental models) about their integration and their tasks to a higher extent than non‐network ones. They were also individually more satisfied of their job and displayed higher work engagement than non‐network workers. Beneficial team‐related dynamics, such as perceived interdependence, were responsible for the differences between the Hub‐and‐Spoke workers and non‐network ones. The implications of the present findings were discussed in terms of promotion of health workers' satisfaction and well‐being.